SUBSTANDARD VOCABULARY IN RUSSIANAND ENGLISH-SPEAKING SOCIETIES: GENDER DIFFERENTIATION - Inna Igorevna Lizenko (Вестник Северо-Кавказского федерального университета, 2022)
This article is devoted to the problem of gender reflection of unconventional vocabulary in English and Russian languages, in their oral and written forms. The article includes the interpretation of the theoretical questions of gender investigation such as explanation of the terms «gender», «unconventional vocabulary», and description of the lines of gender investigation between the male and female speech.